Associations of internalized and anticipated HIV stigma with returning to work for persons living with HIV. - Joseph S Lightner (Public Library of Science (PLoS), 2021)
Introduction Employment is particularly beneficial for persons living with HIV (PLWH). However, PLWH experiencing internalized stigma or anticipating that they may experience stigma may be less likely to seek employment due to additional barriers associated with HIV. The purpose of this study was to understand the associations between internalized and anticipated stigma and employment barriers for PLWH. Methods Participants (N = 712) from 12 sites across the United States were recruited and interviewed about barriers to employment, HIV stigma, and several other factors related to health. A series of unadjusted and adjusted linear regression models were conducted using cross-sectional data. Results Adjusted models suggest that greater anticipated stigma was related to increased employment barriers (β = 0.12, p = 0.04). Mental and physical health functioning also positively predicted employment barriers (β = -0.18, p <0.001; β = -0.40, p <0.001, respectively). Discussion Employment among PLWH has beneficial impacts on HIV-related health outcomes. This study suggests that anticipated stigma may limit and individual's willingness to seek out employment, or may cause them to leave employment. Internalized stigma may not play as large of a role in employment as anticipated stigma for PLWH. HIV-related stigma reduction interventions focused on community-level and employers are essential to improve employment opportunities for PLWH.